RADIOSHIELDING PROPERTIES OF THE ELECTROMAGNETIC SHIELD BASED ON MOISTURE CONTAINING EXPANDED CLAY - S. E. Savanovich; V. B. Sokolov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results on the effect of concentrations of aqueous solutions of sodium chloride on the radio shielding characteristics moisture containing expanded clay in the frequency range 0.7...17 GHz are investigated.